The intricate role of mast cell proteases and the annexin A1-FPR1 system in abdominal wall endometriosis - Paula Júnior, Rubens [UNESP]; Oliani, Antonio Hélio; Vaz-Oliani, Denise Cristina Mos; D'Ávila, Solange Corrêa Garcia Pires; Oliani, Sonia Maria [UNESP]; Gil, Cristiane Damas (My University, 2014)
Endometriosis is a continuous and progressive disease with a poorly understood aetiology, pathophysiology and natural history. This study evaluated the histological differences between eutopic and ectopic endometria (abdominal wall endometriosis) and the expression of mast cell proteases (tryptase and chymase), annexin A1 (ANXA1) and formyl peptide receptor 1 (FPR1). Ectopic endometrium from 18 women with abdominal wall endometriosis and eutopic endometrium from 10 women without endometriosis were obtained. The endometrial samples were analysed by histopathology, immunohistochemistry and ultrastructural immunogold labeling to determine mast cell heterogeneity (tryptase and chymase positive cells) and the expression levels of ANXA1 and FPR1. Histopathological analysis of the endometriotic lesions showed a glandular pattern of mixed differentiation and an undifferentiated morphology with a significant influx of inflammatory cells and a change in mast cell heterogeneity, as evidenced by a significant increase in the number of chymase-positive cells and endogenous chymase expression. The undifferentiated glandular pattern of endometriotic lesions was positively associated with a marked increase and co-localization of ANXA1 and FPR1 in the epithelial cells. In conclusion, the co-upregulated expression of mast cell chymase and ANXA1–FPR1 system in ectopic endometrium suggests their involvement in the development of endometriotic lesions.
Keywords: Chymase; Endometrioma; Immunohistochemistry; Inflammation; Lipocortin-1; Transmission electron microscopy